Effects of Indoor Air Purifiers on Children with Asthma - Lee, Ga Hee (Yonsei Med J, 2020)
PURPOSE: To evaluate the effects of air purifiers on the concentrations of indoor air pollutants and on asthma control in children. MATERIALS AND METHODS: In this randomized crossover trial, daily use of an air purifier filter was compared with a matched placebo with the filter off. Thirty elementary school students who had asthma were enrolled and randomly allocated to one of two groups. The primary endpoints were changes in indoor air quality, asthma severity, lung function, airway inflammatory, urine microbiome, and phthalate after the installation of air purifiers. PM(2.5) and CO(2) were measured as indoor air pollutants. Asthma severity was assessed in terms of both symptom and medication scores acquired using a daily questionnaire. The higher the score, the better the symptom or the less frequent the use of medication. Peak expiratory flow rate and fractional exhaled nitric oxide were also measured. RESULTS: The mean age of the enrolled patients was 9.2±1.98 years. The mean concentration of PM(2.5) was 17.0 µg/m(3) in the filter-off condition, but significantly lower at 9.26 µg/m(3) in the filter-on condition. Medication scores were 6.9 for the filter-off and 7.12 for the filter-on conditions, reflecting a statistically significant decrease in the frequency of medications used during air purifier operation. Bacterial richness, as determined using the Chao 1 index, was markedly lower in the filter-on than the filter-off condition. CONCLUSION: This study suggests that air purifiers benefit medication burden in children with asthma by reducing PM(2.5) levels.